Concomitant cellulase and amylase production by a thermophilic bacterial isolate in a solid-state fermentation using rice husks - Iqbalsyah, Teuku M.; Amna, Ulil; Utami, Rika Sri; Oesman, Frida; -, Febriani (Agriculture and Natural Resources, 2019)
Solid-state fermentation using agricultural waste may induce the secretion of multiple extracellular enzymes, making it a good option for more effective enzymes production. This study investigated the simultaneous production of cellulase and amylase using solid-state fermentation in rice husk media with a local thermophilic isolate. Coarse and milled husks (>25 mesh, 25–50 mesh and <50 mesh) were used as the raw materials. The effects were evaluated of moisture content, incubation temperature and incubation time on the production of the enzymes. Cellulase and amylase were produced mainly simultaneously with the various particle sizes. However, a smaller particle size produced enzymes with the highest activities but lowest specific activities. The optimum activities of cellulase and amylase were observed on the medium with a particle size less than 50 mesh (0.30 mm). The medium with 70% moisture content had the highest cellulase and amylase activities. Variation of the incubation temperature showed that the enzymes were best produced at 70°C for 72 hr. Thus, rice husks are a potential raw material for simultaneous cellulase and amylase production.